Maximizing Sales: The Effect of Instagram, Brand Ambassadors and Product Quality - Puspitasari, Ika Juindri; Muslikh (Marketing and Business Strategy, 2025)
This study investigates the influence of Instagram social media, brand ambassadors, and product quality on purchasing decisions for specific skincare products, incorporating an Islamic perspective. The novelty lies in its integration of these factors while emphasizing the dominant role of product quality over social media influence. Using purposive sampling, the study surveyed 100 respondents. Data analysis was conducted through multiple regression analysis, including t-tests and F-tests. The results revealed that (1) Instagram has a positive but marginal impact on purchasing decisions, (2) brand ambassadors also have a slight positive effect, and (3) product quality has a significant and positive impact on consumer decisions. Furthermore, all variables collectively have a significant influence on purchasing behavior. From a managerial perspective, these findings suggest that businesses should leverage Instagram by producing visually engaging content that resonates with their target audience. Additionally, selecting brand ambassadors who align with the company’s values and exhibit strong social influence can improve brand credibility and consumer trust. Most importantly, focusing on product quality, in accordance with Islamic values of honesty and integrity, plays a crucial role in shaping consumer choices and fostering long-term brand loyalty.